Strategi Optimasi Jaringan Distribusi Sampah Organik di Tangerang Selatan - Didin Jamaludin; Heti Mulyati; Alim Setiawan Slamet (IPB University, 2022)
South Tangerang City is the youngest city that officially separated from the Tangerang Regency in 2008. Area of South Tangerang City 147,19 km2 or 1,63 percent from the area of Banten Province with the widest area of Pondok Aren subdistrict with an area of 2.988 hectares. While administratively, South Tangerang City has 7 sub-districts namely Pamulang, Setu, Ciputat, East Ciputat, Serpong, North Serpong and Pondok Aren, and has 54 villages. Optimizing the distribution network of organic waste supply chain can be formulated in Vehicle Routing Problem (VRP) model. Variants of VRP include Capacitated Vehicle Routing Problem (CVRP) can be used as a model in optimizing the waste transport route and the determination of the fastest route for the transport process of organic waste in all intermediate transfer points spread in South Tangerang city. The results of this research formulate some models of optimization organic waste transport routes in each sub-district in South Tangerang city. As in Setu district there is one optimum route, Serpong district there are 7 optimum route, Pamulang district have 6 optimum route, Ciputat district have 3 optimum route, East Ciputat District have 1 optimum route, Pondok Aren district have 4 optimum route, North Serpong there are 2 optimum routes.